The Issues Concerning the Management of Cross-Border EU Projects During the Covid-19 Pandemic - Agnieszka MALKOWSKA; Karolina DRELA (Communications of International Proceedings, 2020)
The aim of the research was to identify problems of Polish-German cross-border cooperation during the COVID-19 pandemic, including those related to the implementation of projects under the Interreg programmes. The research carried out in the article was based on quantitative secondary data, primary information and analysis of available source literature. The research methods used in this paper include: critical analysis of the source literature, the method of secondary data analysis and the method of in-depth interviews. The purpose of the article is to indicate the degree of implementation of the selected, Polish-German cross-border cooperation Interreg programme, to identify related problems resulting from the COVID-19 pandemic and to assess their impact on the effects of the cooperation. The identified problems include: delays in the implementation of subsequent stages of the project; failure to achieve all the effects of the project, including e.g. indicators of the number of people participating in the planned activities; problems with the organisation of the required tenders; problems with the financial liquidity of partners implementing the project or the need to replace on-site activities with online forms. The analysis and assessment carried out in the article indicated that the COVID-19 pandemic and its consequences have affected in particular border areas of the European Union and their inhabitants, and have adverse effects on cross-border cooperation, including on the implementation of joint projects. The results obtained may be used to develop programmes to counter the effects of the crisis in border areas and in the implementation of EU programmes carried out as part of cross-border cooperation.
Keywords: management of cross-border; project management; Covid-19; pandemic; EU